VD_FINDINFO 15/2014 vom 30. Januar 2014 - VD Tribunal cantonal (2014)
ADMISSION DE LA DEMANDE, DROIT TRANSITOIRE, AUTORITÉ DE RECOURS, RÉCUSATION | 222 CPC, 42 CPC, 44 CPC, 404 al. 1 CPC (CH), 405 al. 1 CPC (CH), 50 al. 2 CPC (CH), 8a al. 3 CDPJ